Entrepreneurship Education and Digital Marketing for Improving the Welfare of the Community – A Case Study on Gada Village, Gunungsitoli Regency, Nias - Muhammad Isa Indrawan; Husni Muharram Ritonga; Dian Septiana Sari (CV. AFDIFAL MAJU BERKAH, 2022)
Community welfare is an inseparable part of the paradigm of economic development, economic development is said to be successful if the level of community welfare is getting better. Gaps and inequality in people's lives are caused by the success of economic development that is not accompanied by an increase in people's welfare. One of the villages that has the potential for natural and cultural village tourism that can be maximized is Gada Village, located in Gunungsitoli Regency, Nias. Gada Village is one of nine villages located in West Gunungsitoli District, Gunungsitoli City, North Sumatera Province. Data analysis was carried out through PLS-SEM using the Smart PLS 3 program. The results showed that entrepreneurship education had a positive and significant effect on digital marketing. Entrepreneurship education has a positive and significant impact on people's welfare. Digital marketing has a positive and significant impact on people's welfare. Entrepreneurship education has a positive and significant impact on people's welfare through digital marketing.